-8w+24=-6(w-2)

Simple and best practice solution for -8w+24=-6(w-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8w+24=-6(w-2) equation:



-8w+24=-6(w-2)
We move all terms to the left:
-8w+24-(-6(w-2))=0
We calculate terms in parentheses: -(-6(w-2)), so:
-6(w-2)
We multiply parentheses
-6w+12
Back to the equation:
-(-6w+12)
We get rid of parentheses
-8w+6w-12+24=0
We add all the numbers together, and all the variables
-2w+12=0
We move all terms containing w to the left, all other terms to the right
-2w=-12
w=-12/-2
w=+6

See similar equations:

| 22-2x=13+7x | | 7n+8=2n | | 7(v+2)=9v+4 | | 5x+35=-4x+10 | | -6x-7=5(x+3) | | 10y+5y=15 | | -8(x+5)=3x+25 | | 32=-2t | | 7x+1/2=141/2 | | 9x-11+3x+5=180 | | 2^x=2.44 | | |2x+1|=0 | | 81y*2X=72 | | 3(2k-2)=-2(4-11) | | x+7÷5=3x | | m2=16/9 | | -1=(-4/7t) | | S+b=-11 | | 12=-2(x-8) | | 5/x+6/x= | | 0=3t^2-40t+128 | | -4(3x+6)=48 | | 12x2–x–6=0 | | -y+(-8y)=-9 | | 3x2+9x–2=0 | | (2x-24)+86=180 | | 12+3w=42 | | x+5.9=2.9 | | 35=-9x-10 | | 6x-3=67 | | 0.25÷3=x÷3/2 | | (3/(2x-1))+(4/(x+2))=2 |

Equations solver categories